AN ANALYSIS OF THE GUITAR MUSIC LEARNING OF BEGINNER USING PROBLEM-BASED LEARNING - Abraham G. A. Onibala; Meyny Kaunang; Franklin Dumais (Faculty of Language and Arts (Fakultas Bahasa dan Seni) Universitas Negeri Manado, 2023)
This present study aims at exploring the implementation of Beginner Guitar Music Learning through the application of the Problem Based Learning (PBL) model. The research focuses on understanding how the Problem Based Learning model is employed in the context of learning beginner guitar music. The qualitative method with a pedagogical approach was employed for data collection, utilizing observation, interviews, and documentation. The findings reveal that, in the preparatory phase for implementing music learning activities at SMA Negeri 1 Tondano, comprehensive planning is essential. This involves developing semester programs, syllabuses, lesson plans, learning media, and teaching materials. Moreover, the cultural arts (music) teachers conduct a thorough assessment of each student's abilities, considering their interests, needs, and profiles. This information aids in tailoring the learning process to accommodate different learning styles. The study contributes valuable insights into the practical application of the Problem Based Learning model in the domain of beginner guitar music education.